Plans and Environment for kennels - Jaume Camps Rabadà (Derecho Animal, 2015)
This document studies in the first place, dogs Environmental and basic Needs in order to analyze in detail the kennels, to make a proposal of a model kennel explaining how kennel floors and foundations, walls and fencing , the roof, etc. should be, in order to provide a good Animal Welfare standard.